Profitable Production as a Socio-Economic Based on Supply Chain Management with Lean Production - Larisa A. Tretyakov?; Marina V. Vladika; Tatyana V. Tselyutina; Tatyana A. Vlasova; Olga A. Timokhina (International Journal of Supply Chain Management, 2020)
Abstract— The article discusses organizational, economic and managerial relations that determine the supply chain management and the system of elements of “lean production” in human resource management. The essence and interrelation of the management system of organizational behavior and elements of corporate Lean culture are revealed, the possible directions of the influence of lean production culture on the organizational behavior of employees, considering the specifics of the personnel management of a particular organization, are substantiated. It was concluded that the basis of the strategy of managing organizational behavior should be a “lean” approach, involving the creation of a corporate culture of lean manufacturing, conditions for managing group work, corporate communications, managing teams, and leaders able to unlock the potential of employees. The main principles of a lean approach are: “sustainable socio-economic development is transformation in the minds and actions of personnel” and “lean synergy is a factor and resource for increasing productivity”.